The Influence of Trust on Purchase Intention with the Theory of Planned Behavior as an Intervening Variable at Teratai Clinic - Purwani, Benedicta Feby; Tcoalu, Melitina; Assa, Adrie Frans (Syntax Corporation, 2026)
The growing demand for in vitro fertilization (IVF) services in Indonesia poses challenges for fertility clinics, including the experienced Teratai Clinic since 2006. Fluctuating success rates and high costs erode patient trust and purchase intention. This study examines trust's influence on purchase intention, using the Theory of Planned Behavior (TPB) as an intervening variable in IVF services at Teratai Clinic. A quantitative approach distributed questionnaires to IVF patients via purposive sampling. Data analysis employed Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS software. Results show trust positively affects purchase intention (-statistic = 2.686; = 0.007), TPB (-statistic = 2.698; = 0.007), and TPB influences purchase intention (-statistic = 3.290; = 0.001). TPB mediates trust's effect on purchase intention (-statistic = 3.709). Findings highlight trust-building via information transparency, medical credibility, and service quality to boost IVF interest. Practical implications urge Teratai Clinic to enhance digital communication, testimonials, and innovations for sustainable trust. Theoretically, the study advances consumer behavior research by positioning TPB as a psychological bridge between trust and purchase intention.